Real-time parameter estimation of servo-pneumatic system - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY PRESS, 2007)
An experiment based method is proposed for parameter estimation of a class of servo pneumatics system. The method was applied to a linear servo-pneumatic actuator. Experimental time domain input/output data was utilized in a gray-box modeling approach. Prior knowledge of the form of the system transfer function elements is assumed to be known. Continuous-time system transfer functions parameters were estimated in real-time by the least-squares method. Simulation results of experimentally determined system transfer function compare very well with the experimental results. The proposed method can be implemented conveniently on a desktop PC equipped with a data acquisition board for parameter estimation of moderately servo pneumatics system. The interface is designed and tested in MATLAB/Simulink using the Real Time Toolbox.
Keywords: parameters estimation real-time; servo pneumatic system